AB0485 Serum 25(oh) vitamin d levels, body mass composition and extent of skin sclerosis in systemic sclerosis patients. (23rd January 2014) - Corrado, A.; Neve, A.; Marucci, A.; Colia, R.; Mele, A.; Cantatore, F. P.
Abstract : Background: Low Vitamin D concentrations have been reported in several rheumatic autoimmune diseases, and represent a key factor in determining the reduction of bone mass density (BMD) and increased fracture risk in rheumatic patients. In Systemic Sclerosis (SSc), hypovitaminosis D is frequently observed, although the available data appear to be somewhat discordant. The origin of hypovitaminosis D in SSc is multifactorial and includes reduced sun exposition, malnutrition, reduced physical activity, and pharmacological interactions. Nevertheless, the possible relationship between specific clinical findings in SSc patients and low serum levels of vitamin D are not yet fully investigated. Particularly, the possible influence of skin thickness on serum Vitamin D levels has not be explored Objectives: The aim of this study is to evaluate the relationship between BMD, body mass composition, skin sclerosis and serum Vitamin D levels in two subsets of SSc patients. Methods: 55 post-menopausal SSc patients (mean age 65±10, 34), classified according to Leroy as limited (lSSc) or diffuse (dSSc) were studied. For each recruited patients clinical parameters, including the modified Roadnan Skin score and the body mass index (BMI), were evaluated. Spine and hip bone mass density (BMD) and body mass composition (total body mass, lean mass, fat mass, body mineral content) were determined by dual-energy X-ray absorptiometry. Serum calcium, phosphorus, alkaline phosphatase, osteocalcin, urine pyridinium cross-links, intact parathyroid hormone (PTH) and 25-hydroxyvitamin D (25 OHD) were also measured Results: In dSSs, BMD (spine, femoral neck and total hip) was significantly lower compared to lSSs (p<0.05). Total body mass was significantly lower in dSSc, (p<0.05) with no differences in both fat and lean mass in the two study groups; conversely, body mineral content (BMC) was significantly reduced in dSSc patients (p<0.05). In both groups, hypovitaminosis D was observed (mean 25OHD 16, 8±9, 7), but 25OHD serum levels were significantly lower in dSSc (p<0.01) and inversely correlated with the extent of skin thickness (r= -0, 46, p<0, 05). No differences between lSSc and dSSc in serum calcium, phosphorus, alkaline phosphatase, osteocalcin, urine pyridinium cross-links and PTH were found. Conclusions: A greater reduction of BMD in dSSc compared to lSSc has been reported by several authors; nevertheless the possible factors involved in bone loss are not fully investigated, particularly in regards to hypovitaminosis D. These results support the hypothesis that the extent of skin involvement in SSc patients could be an important factor in determining low circulating levels of 25OHD, which in turn could play a significant role in the reduction of BMD and BMC. References: Arnson Y et al. Serum 25-OH vitamin D concentrations are linked with various clinical aspects in patients with systemic sclerosis: a retrospective cohort study and review of the literature. Autoimmun Rev. 2011 Jun;10(8):490-4 Frediani B et al. Clinical determinants of bone mass and bone ultrasonometry in patients with systemic sclerosis. Clin Exp Rheumatol. 2004 May-Jun;22(3):313-8 Disclosure of Interest: None Declared